The Impact of Firm Characteristics on Quality of Risk Disclosure in UK FTSE 100 Non-financial Firms - Wu, Peiying (2017)
Changing environment and adverse effects of current and potential risks on firm operations have raised more concern from stakeholders and have increased their needs for corporate risk disclosure. This dissertation will examine the impact of five firm characteristics, including firm size, risk level, profitability, firm growth and leverage, on quality of risk disclosure. A sample is selected from UK FTSE 100 non-financial firms since there is a voluntary disclosure environment in the UK and fewer disclosure requirements are imposed on non-financial firms. This could reduce the impact of compulsory regulations on incentives of managers’ risk reporting. Quality is a complex concept which cannot be measured merely through quantity and it could be measured through different dimensions. A composite variable produced through factor analysis in this dissertation is used to measure quality of risk disclosure by considering not only quantity indicator, but also coverage, depth and outlook profile aspects of quality. The main findings include a positive association between quality of risk disclosure and firm growth and a negative relationship between quality of risk disclosure and firm risk level while no correlation is found between quality of risk reporting and other firm characteristics. This dissertation has also contributed to studies of quality of risk disclosure compared to most prior literature with consideration of the quantity of risk reporting. There is a limitation to link the regression results with relevant literature to support the impact of corporate characteristics on quality of risk disclosure. Hence, more research contributions and further developments in the study field of quality of risk disclosure are needed in the future.